2018
DOI: 10.2196/publichealth.8950
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Influenza Monitoring and Forecasting Using Novel Internet Data Streams: A Case Study in the Boston Metropolis

Abstract: BackgroundInfluenza outbreaks pose major challenges to public health around the world, leading to thousands of deaths a year in the United States alone. Accurate systems that track influenza activity at the city level are necessary to provide actionable information that can be used for clinical, hospital, and community outbreak preparation.ObjectiveAlthough Internet-based real-time data sources such as Google searches and tweets have been successfully used to produce influenza activity estimates ahead of tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
89
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 29 publications
1
89
0
1
Order By: Relevance
“…Previous work has shown the versatility of ARGO, one of the component models in our ensemble, 152 over a variety of disease estimation scenarios [5,[20][21][22]. At the state level, where it had not been applied 153 before, it clearly outperformed existing benchmarks over the study period, namely Google Flu Trends 154 and an autoregression.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Previous work has shown the versatility of ARGO, one of the component models in our ensemble, 152 over a variety of disease estimation scenarios [5,[20][21][22]. At the state level, where it had not been applied 153 before, it clearly outperformed existing benchmarks over the study period, namely Google Flu Trends 154 and an autoregression.…”
mentioning
confidence: 94%
“…Established influenza reporting systems currently exist over large geographic scales in 18 the United States, coordinated by the Centers for Disease Control and Prevention (CDC). These systems 19 provide weekly reports of influenza statistics, aggregated over the national, regional (10 groups as defined by 20 the Health and Human Services), and starting in fall 2017, state level. Of particular interest, U.S. Outpatient 21 Influenza-like Illness Surveillance Network (ILINet) records the percentage of patients reporting to outpatient 22 clinics with symptoms of influenza-like illness (ILI), which is defined by fever over 100°F in addition to sore 23 throat or cough, over the total number of patient visits [4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Brooks et al's top-performing entry [4] to the CDC's flu forecasting challenge [9] was improved by nowcasting. Lu et al tested autoregressive nowcasts using several internet data sources and found that they improved 1-week-ahead forecasts [23]. Kandula et al measured the benefit of nowcasting to their flu forecasting model at 8-35% [21].…”
Section: Introductionmentioning
confidence: 99%